Function of the fliK Gene in Pseudomonas plecoglossicida Pathogenicity and Epinephelus coioides’ Immune Response - Liu, Zixu; Yuan, Biao; Zhao, Lingmin; Huang, Lixing; Qin, Yingxue; Zhang, Jiaonan; Zhang, Jiaolin; Hu, Bing; Yan, Qingpi (Frontiers in Marine Science, 2022)
Pseudomonas plecoglossicida is a gram-negative pathogenic bacterium that causes visceral white spot disease in several marine and aquaculture fish species, resulting in high mortality and severe financial loss. Based on previous RNA sequencing (RNA-seq), fliK gene expression is significantly up-regulated in P. plecoglossicida during infection, indicating that fliK may contribute to its bacterial pathogenicity. To investigate the role of fliK, four specific short hairpin RNAs (shRNAs) were designed and synthesized according to the fliK gene sequence, with three of the four mutants exhibiting a significant decrease in fliK gene expression in P. plecoglossicida. The shRNA-406 mutant with the maximum silencing efficiency (97.5%) was chosen for further study. Compared with the wild-type (WT) P. plecoglossicida strain, silencing fliK in the fliK-RNA interference (RNAi) strain resulted in a significant decrease in growth, motility, chemotaxis, adhesion, and biofilm formation in P. plecoglossicida. Silencing of fliK also resulted in a 95% increase in the survival rate, a 2-day delay in the onset of death, and a significant decrease in the number of white spots on the spleen surface in infected orange-spotted groupers (Epinephelus coioides). In addition, fliK gene expression and pathogen load were significantly lower in the spleens of E. coioides infected with the fliK-RNAi strain than in those infected with the WT strain of P. plecoglossicida. RNA-seq of the spleens further revealed that fliK silencing significantly regulated the immune response of E. coioides during the pathogenic process. Compared with the WT-infected group, the differentially expressed genes (DEGs) in the fliK-RNAi-infected group were enriched in 344 and 345 KEGG pathways at 3 and 5 days post infection (dpi), respectively. Among these pathways, 21 immune system-related pathways were enriched, including the natural killer (NK) cell-mediated cytotoxicity, platelet activation, and Th17 cell differentiation signaling pathways. The NK cell-mediated cytotoxicity pathway was the most significantly enriched, which may enhance the host’s ability to remove pathogens and reduce inflammation. This study revealed the effects of the fliK gene in P. plecoglossicida pathogenicity and identified the main pathways involved in the immune response of E. coioides.